THE COURAGE OF ARABIC- THE STYLE OF ATTENTION AS AN EXAMPLE (American Journal of Research in Humanities and Social Sciences, 2023)
The concept of Arabic courage is an aesthetic and rhetorical concept that allows revealing the nature of the language when used for aesthetic purposes, allowing the reader to realize how creativity is achieved. There are many wonderful stylistic deviations, according to Ibn Jinni, but the most beautiful thing about it is politeness in its expression and purposes, and the sweetest thing about it is its duality. Regarding the method of paying attention that we discussed in our research as a model of Arabic courage, , most of the rhetoric stressed that if the speech came to one method and it took a long time to change the method. This is how they used to pay attention to the listener's activity and entice him to listen, but we discovered that Ibn Jinni had a different criterion in his view of this method, as he was the first to notice that paying attention is not a phenomenon with which one is satisfied. Attention is a multiplication of the language's expansion to move from one word to another. Rather, it is a stylistic phenomenon involving a dependent purpose and following the example to which the hand is tied.